Assessment of Beliefs, Behaviors, and Opinions About Blood Donation in Telangana, India—A Cross Sectional Community-Based Study - Samreen, Sana; Sales, Ibrahim; Bawazeer, Ghada; Wajid, Syed; Mahmoud, Mansour Adam; Aljohani, Majidah A. (Frontiers in Public Health, 2021)
Background and Objectives: Blood is an essential body fluid primarily required for regulating the body's systems and maintaining homeostasis. In developed and developing countries, concern about the demand and supply for blood is increasing. The current study aims to assess the beliefs, behaviors, and opinions of the public toward blood donation. Methods: This was a cross-sectional study in which a self-created questionnaire with 17-items was used for data collection. The self-administered questionnaire was disseminated between November 2019 and January 2020 through social media (WhatsApp© and Facebook©). Data was analyzed using SPSS program version 26. Results: A total of 356 questionnaires were completed with a response rate of 89%. The majority of participants were male 253 (71.1%), 336 (94.4%) considered blood donation important, 350 (98.3%) believed that blood donation saves lives, and 254 (71.3%) agreed to receive blood from voluntary donors. One-hundred sixty-seven (49.4%) were willing to donate blood voluntarily. The barriers to blood donation were fear of needles 86 (24.2%), fear of contracting a chronic disease 84 (23.6%), and lack of time 40 (11.2%). One day off (91.9%) and receiving a token 73.6% were common motivational factors for blood donation. Overall, 57% of the participants had favorable attitudes toward blood donation and 41.9% were knowledgeable. Favorable attitudes were significantly associated with being married (P = 0.018) and having university level of education (P = 0.005). Younger participants (18–29 years) had a statistically significant better knowledge than older participants (≥30 years). Conclusion: The respondents displayed positive beliefs, opinions, and motivation toward blood donation. Additionally, most of them considered blood donation an important act and a national duty of every individual and are willing to donate in the future.